E-cigarettes, conventional cigarettes, and dual use in Korean adolescents and university students: Prevalence and risk factors. (1st November 2016) - Jeon, Christina; Jung, Keum Ji; Kimm, Heejin; Lee, Sungkyu; Barrington-Trimis, Jessica L.; McConnell, Rob; Samet, Jonathan M.; Jee, Sun Ha
Highlights: Current/lifetime cigarette only, e-cigarette only, and dual use rates were compared. Peer smoking was the covariate most strongly associated with e-cigarette only use. Males were more likely to engage in the smoking behaviors than females. Abstract: Objective: To examine risk factors associated with use of e-cigarettes only, conventional cigarettes only, and dual use in Korean adolescents and young adults. Methods: In a cross-sectional study, anonymous questionnaires were completed between April–May, 2015 among 1) 2744 middle and high school students, aged 13–18, from Seoul, Incheon, Gyeonggi, and Cheongju, Korea and 2) 2167 university students, aged 19–29, from fourteen universities in Korea. Results: The results show that 12.6% of adolescents and 21.2% of university students reported having ever tried e-cigarettes at least once. Among the ever e-cigarette users, 95.1% and 96.3% of adolescents and university students also tried conventional cigarettes, respectively. Dual users were more likely to be male (adolescents: OR 2.63, 95% CI 1.93–3.57; university students: 4.28, 3.21–5.70), have any close friends who smoke (adolescents: 11.56, 7.63–17.53; university students: 11.29, 5.52–23.10), have any siblings who smoke (adolescents: 3.17, 2.25–4.46; university students: 1.78, 1.30–2.43), and have observed teachers smoke cigarettes at school (adolescents: 1.45, 1.05–2.01). Conclusions: A majority of e-cigarette users were dual users. Friends' and siblings' smoking status were significantly associated with dual product use in adolescent and young adult populations. Surveillance of e-cigarette use and implementation of evidence-based behavioral interventions targeting adolescents and young adults are necessary.